Efforts of Sat Samapta Patrols Performance Improvement to Prevent Motor Vehicle Theft in the Jurisdiction of Boyolali Police Resort - Putra, Muhammad Fadly Iwan (Police Studies Review, 2024)
The background for writing this thesis is the increasing number of motor vehicle theft crimes in the Boyolali Police Legal Area in 2022 compared to 2021. By prioritizing preventive methods, the Samapta Unit makes efforts to prevent the crime of motor vehicle theft in the Legal Area of the Boyolali Police by conducting patrols to prevent the emergence of intentions and opportunities to commit crimes. The purpose of this paper is to describe and analyze the organizational resources and implementation of the Samapta Patrol in preventing the crime of motor vehicle theft in the jurisdiction of the Boyolali Police. As an analytical tool, the author uses several concepts and theories, namely: the concept of performance, the concept of Patrol, the concept of the Samapta unit, the concept of theft, the theory of management, the theory of elements of management, the theory of SWOT, and the theory of crime prevention. With the research area in the jurisdiction of Boyolali Police Resort. This research was carried out with a qualitative approach, using field research types, as well as data collection techniques by observation, interviews, and document studies. The results of this study, the researchers found facts about the condition of organizational resources and the implementation of Satsamapta patrols, namely the quality and quantity of Satsamapta personnel was inadequate, the administration was still not appropriate, the implementation of patrols was not in accordance with the time prone to theft, the implementation of patrols was only for formality, and not yet intensive communication between Satsamapta and Satreskrim related to the anatomy of motor vehicle theft. The researcher concludes that the organizational resources and implementation of patrols in preventing motor vehicle theft are still not optimal. Therefore the author provides input so that the Satsamapta Polres Boyolali provides training related to patrols to increase the knowledge and abilities of members as well as socialization of patrols by the head of the Turjawali unit in accordance with the Perkap. In addition to repairing and supervising the administration of patrols. Then the efforts that can be made are to rearrange the composition of the patrol members, stricter supervision by superiors, patrol targets adjusted to the time and place where motor vehicle theft is prone to occur, and intensive coordination with the Criminal Investigation Unit related to the anatomy of motor vehicle theft every month, as well as conducting patrols intersect with the sector Police.